Evaluation of Industrial By-Products as Sustainable Pozzolanic Materials in Recycled Aggregate Concrete - Alnahhal, M.F.; Alengaram, Ubagaram Johnson; Jumaat, Mohd Zamin; Alqedra, M.A.; Mo, Kim Hung; Sumesh, M. (MDPI, 2017)
The utilization of traditional supplementary cementitious materials (SCMs) has become more intense in the concrete industry due to their better long-term properties. This research evaluates the fresh and hardened properties of concrete that was developed using a high amount of recycled aggregate (RA) incorporated with sustainable SCMs. Rice husk ash (RHA), palm oil fuel ash (POFA) and palm oil clinker powder (POCP) were used as SCMs at 10%, 20% and 30% cement replacement levels to investigate their positive role in the performance of RA concrete. The results showed that the 10% replacement level of cement by RHA produced the highest strength at all ages tested. Although POFA and POCP were found to negatively affect the strengths at an early age, the hardened properties showed improvement after a relatively long curing time of 90 days. In addition, the targeted compressive strength of 30 MPa was achieved by using SCMs at levels up to 30%. Overall, the sustainable SCMs can reduce the quantity of cement required for concrete production, as well as reduce the conventional cement with the industrial by-products, which are considered as waste materials; thus, the concrete produced using up to 30% of SCMs as a replacement for cement could be considered as more environmentally-friendly concrete.